136 Readmissions to Hospital Following A Decision to Eat and Drink with Acknowledged Risk with Support From the Forward Care Bundle. (16th March 2021) - Soar, N; Birns, J; Sommerville, P; Lang, A; Fitzgerald, A; Archer, S
Abstract: Introduction: The FORWARD care bundle (Feeding via the Oral Route With Acknowledged Risk of Deterioration) is used to support patients with dysphagia eating and drinking with acknowledged risk (EDAR) at our Trust. Key aims of FORWARD include improving advanced care planning (ACP) and avoiding unnecessary readmissions. This study aimed to determine the incidence of EDAR related readmissions (RR-EDAR) after FORWARD, and the effects of ACP and discharge location. Methods: Retrospective review of all patients supported by FORWARD during admissions between January 2018 and December 2019. Data were collected on number and reasons for in-Trust hospital readmissions 6 months post-discharge, preferred place of care ACPs in event of EDAR related deterioration and discharge destination. Readmission reasons were classified as RR-EDAR (e.g. chest infection, reduced oral intake) and no relation to EDAR. Means (SD) and percentages are presented with comparisons using Fishers Exact Test. Results: 316 patients were included; mean (SD) age 81(12). 64% (n = 202) of patients were discharged alive, 36% (n = 114) were alive at 6 months. 38% of live discharges (n = 75) were readmitted and 52% (n = 39) of these patients were RR-EDAR. Mean (SD) RR-EDAR number was 11, and 18% (n = 7) of patients had RR-EDAR >1 (range 1–5). RR-EDAR was only 7% (n = 4) in patients wishing to remain at home vs 25% (n = 33) in those without a documented place of care (p < 0.01). RR-EDAR was 23% (n = 29) in patients discharged to a private home vs 10% (n = 6) discharged to nursing/care homes (p < 0.05). Conclusions: The majority of FORWARD patients are not readmitted. RR-EDAR comprises half of all readmitted patients and some have multiple admissions. Fewer patients with ACPs were RR-EDAR suggesting these are effective. Most patients RR-EDAR were from private homes, suggesting residential care may provide more support. Further work includes increasing ACPs, supporting patients with multiple RR-EDAR and those discharged to private homes.